Elicitor recognition, signal transduction and induced resistance in plants - Mishra, A.K.; Sharma, K.; Misra, R.S. (Informa UK Limited, 2012)
The most viable and practical option for the management of plant diseases is disease resistance. However, in most of the crop plants, natural resistance against pathogens is rare. Breeding resistant varieties is a long-term process and the possibility of resistance being broken always exists. Induced resistance exploiting natural defense machinery of plants is indeed an alternative, nonconventional and ecologically friendly approach for plant protection. Its introduction into agricultural practice could minimize the scope of chemical control, thus contributing to the development of sustainable agriculture. Induced resistance can be defined as an increased expression of natural defense mechanisms of plants against various types of pathogens, provoked by a range of factors: pathogens causing hypersensitive necrotic reaction, avirulent or attenuated pathogenic strains, and elicitors of pathogenic origin (glucans, proteins, lipids, etc.). Induced resistance, being based on the expression of latent genetic information present in plants, is not underlaid by genome alterations (mutations, introgression of foreign genetic material), thus enhancing its biological safety. In this communication, classes of elicitor, their signal perception, transduction and induced defense gene activation has been described.